Pengaruh Kedaulatan Negara dan Yurisdiksi Mahkamah Pidana Internasional Terhadap Efektivitas Penegakan Hukum Atas Kejahatan Internasional - Anjar Rusadi; Dwi Putri Lestarika; Wevy Efticha Sary (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines the interplay between the principle of state sovereignty and the jurisdiction of the International Criminal Court (ICC) in enforcing law against international crimes. Using a normative-qualitative method and literature review approach, the research finds that state sovereignty is no longer absolute due to the evolution of international law, particularly in human rights protection. The ICC serves as a complementary mechanism (complementarity) when national judicial systems are unwilling or unable to prosecute international crimes. However, the ICC's effectiveness remains constrained by political factors and resistance from non-party states to the Rome Statute.